THE ROLE OF GENETIC TESTING IN CLINICAL LABORATORY DIAGNOSTICS OF HEREDITARY DISEASES IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Hereditary diseases pose a significant challenge in pediatric medicine due to their diverse manifestations and potential lifelong consequences. Genetic testing has become an essential tool in clinical laboratory diagnostics, offering insights into the underlying genetic causes of these conditions. This article discusses the principles of genetic testing, its applications in diagnosing hereditary diseases in children, and the challenges and prospects of implementing these technologies in clinical practice.